Measuring, simulation, and evaluation of room impulse responses for acoustical spaces with rectangular geometry - Abarca López, Josué (2025)
In this paper, a closed room with rectangular geometry is selected, in which a comparative study is performed between the acoustical parameters, obtained from the measured room impulse responses using a directional loudspeaker as sound source, and those generated by numerical methods inside a simulation software, where the sound source is omnidirectional. The benefit of approximating an omnidirectional source by the rotation on the horizontal plane of a directional source is also evaluated. Results presented here indicate that the directional loudspeaker can be used to obtain a general characterisation of the acoustics of the room, with error levels that could be tolerated, particularly for midrange frequency bands, with the advantage of representing a low-cost alternative.